Macrophage‐based delivery of anti‐fibrotic proteins alleviates bleomycin‐induced pulmonary fibrosis in mice - Huiying Liu; Cuiping Yang; Yun Gao; Xueli Zhang; Min Wang; Xinting Yu; Weidong Wang; Lixin Xie; Ping Tang; Xiushan Yin; Changqing Bai; Luo Zhang (Wiley, 2023)
Abstract Idiopathic pulmonary fibrosis (IPF) is a fatal interstitial lung disease characterized by chronic, progressive, and fibrotic lung injury. Although remarkable progress has been made toward understanding the pathogenesis of PF, finding more effective treatments for this fatal disease remains a challenge. In this study, we describe an innovative macrophage‐based approach to deliver anti‐fibrotic protein to the lung and inhibit PF in a mouse model of bleomycin (BLM)‐induced lung injury. We engineered macrophages to continuously secrete three types of proteins: interleukin‐10, which prevents inflammation; TGFRcFc, a soluble truncated TGF‐βR2 that blocks TGF‐β; and CD147, which induces matrix metalloproteinases (MMPs) and causes collagen degradation. Infusing these engineered macrophages into the lungs of BLM‐induced PF mouse models in an optimal pattern significantly ameliorated PF in mice. Specifically, the most effective therapeutic outcome was achieved by infusing IL‐10‐secreting macrophages on day 1, followed by TGFRcFc‐secreting macrophages on day 7 and CD147‐secreting macrophages on day 14 into the same mice after BLM treatment. Our data suggest that macrophage‐based delivery of anti‐fibrotic proteins to the lungs is a promising therapy for fibrotic lung disorders.